2015
DOI: 10.5901/jesr.2015.v5n3p279
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparities in Educational Enrolment and Attainment in Sub-Saharan Africa

Abstract: The importance of education in the development of human capital has been broadly acknowledged. It has also been argued that improving access to education is central in the achievement of poverty reduction and other millennium development goals (MDGs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Since then, outof-pocket expenditures have remained high in many sub-Saharan countries (8). With gender disparities in education, economic opportunities, and wages across sub-Saharan Africa (11)(12)(13), it has been shown that women's ability to pay for healthcare and make informed decisions affecting their health are heavily compromised (14)(15)(16). Amu et al (17) argue that access to health insurance for women in this region correlates with education.…”
Section: Sub-saharan Africa Contextmentioning
confidence: 99%
“…Since then, outof-pocket expenditures have remained high in many sub-Saharan countries (8). With gender disparities in education, economic opportunities, and wages across sub-Saharan Africa (11)(12)(13), it has been shown that women's ability to pay for healthcare and make informed decisions affecting their health are heavily compromised (14)(15)(16). Amu et al (17) argue that access to health insurance for women in this region correlates with education.…”
Section: Sub-saharan Africa Contextmentioning
confidence: 99%
“…More of these forms of privileges which are accorded to the male gender is unfair or unjust because it works to the detriment of the females. For instance, certain socio-cultural beliefs and attitudes deprive females of schooling in instances where their families are impoverished [11]. Socialisation is therefore deemed as a strong precursor to women's low level of educational attainment, reducing in females the desire to aspire for higher heights.…”
Section: Men In Gender Workmentioning
confidence: 99%
“…That notwithstanding, research suggests the gender gap in education is most pronounced in sub-Saharan Africa. These educational discrepancies against women have hinged on the beliefs and attitudes of societies in Africa (Dube, 2015). These gender norms place girls' domestic contribution to the home above their personal education.…”
Section: Gender Norms and Valuesmentioning
confidence: 99%